Umami sea: flavoring innovation from fish waste in Gresik district to create sustainable blue economy - Hesti Rahmawati; Reza Astika Wahyu Pramesti; Nada Fariska Danisswari (Academic Letters, 2025)
Gresik Regency, recognized for its rich fishery resources, is experiencing growing difficulties associated with unmanaged fish waste, which has detrimental effects on both the environment and community health. The "Umami Sea" program presents an eco-friendly approach by converting by-products from fish processing—like bones, skin, and offal—into valuable flavoring products through protein hydrolysis. This development is in line with the blue economy principle, focused on lowering marine pollution, creating local revenue, and reducing reliance on artificial additives such as monosodium glutamate. By applying circular economy strategies, fish waste is evolved into a valuable resource, promoting community-led businesses and strengthening economic stability. The initiative encourages the involvement of coastal communities, including fishermen, small and medium-sized enterprises, and young people, while advocating for healthier, sustainable food options. Underpinned by research, technology sharing, and partnerships among local authorities, universities, and non-governmental organizations, "Umami Sea" serves as a model that can be replicated for sustainable management of fisheries waste. Its advancement not only boosts local economies but also reflects global movements toward eco-innovation and sustainable growth in marine sectors.